Creación de una herramienta de voz a texto utilizando un motor de software libre para facilitar la inclución digital en educacion telepresencial a la comunidad no oyente de la Universidad ECCI (2022)
The purpose of this project is to develop a free software prototype tool for assisting hearing-impaired students that struggle with virtual academic environments. This comes from direct experience of the needs of this community using this platform during the Covid-19 restrictions where captions were unavailable during classes so hearing-impaired students required a full-time sign interpreter during classes to communicate accurately with the teacher. The main motivation for this development is to achieve easier adoption of new virtuality use cases, and solve the evident absence of this service since it is not provided by the university. This proposal is born from the Free Software Research hotbed from the ECCI University to dig deeply into voice-to-text technologies as a primary source to conduct a state-of-the-art analysis using different voice-to-text engines in search of the one most suitable for developing a functional prototype of a voice-to-text based web application that allows students and the university free access to a subtitle generation service that can be provided during conferences, speeches, and extracurricular activities. In this document, you will be able to visualize the different proposed phases: analysis, design, implementation, execution, and testing made to the web application in the last part of the document. The conclusions and contributions on further implementation will be reviewed, as well as recommendations for upgrading and scaling up this platform to be widely used by the community.